Collective Intelligence synergizing into individual and business Resilience - Steggemann, Michael (Mercados y Negocios, 2023)
The presence of Collective Intelligence engenders the integrity of the person and the group in the business and thus, synergistically strengthens the collective resilience, understood as the individual and the company’s resilience. Synergistically as shown, is the habit of creative interactively cooperation, so that each element or party increases the effect of the other.